Proposition and Practical Significance of Two Classes of New Teaching Methods and Diversified Assessment During the Coronavirus Disease 2019 Epidemic - Zhao Bin; Cao Jinming (Journal of Current Scientific Research, 2021)
After entering the new century, people are facing a new external environment. Recently human society is coming into knowledge economy era, and the industrial structure has deeply been adjusted. Today, the past teaching method of imparting knowledge and getting people to accept education, or exam-oriented teaching ideas have been unable to keep up with the needs of the development of the Times. In the future, the key point of education is to promote people to understand the knowledge, and grasp rules between things. Based on this, it is particularly necessary for the talents cultivation to adopt a new idea of training. The paper takes the major in mathematics as an example, designs two classes of new teaching methods CT&CL and BOOF with the diversified assessment to cultivate students’ innovative thinking, providing a reference for the other students. The two classes of new teaching methods and the diversified assessment are worthy of further spreading and exercising during the coronavirus disease 2019 epidemic.
Keywords: Innovation；talent training；the new teaching methods；diversified assessment；practical significance